Policing the Cybercrime Script of Darknet Drug Markets: Methods of Effective Law Enforcement Intervention - Jardine, Eric (American journal of criminal justice, 2021)
Darknet drug market participants must complete a distinct cybercrime script if they are to successfully procure illicit substances online. This paper details the four generic stages (i.e. Informational Accumulation; Account Formation; Market Exchange; Delivery/Receipt) of a novel cybercrime script for Darknet drug markets. It also presents vignette examples of known law enforcement interventions that have effectively targeted each stage of the script to reduce usage of these marketplaces. While law enforcement interventions to close specific Darknet markets tend to have only short-lived effects on levels of illicit activity, the lens of the cryptomarket crime script highlights numerous additional steps beyond closure that law enforcement can effectively undertake to reduce use of these platforms.